2009
DOI: 10.1038/eye.2009.74
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of visual recovery with macular height in macula-off retinal detachments

Abstract: Objectives To determine the relationship between the preoperative macular height of a macular detachment and visual outcome of the post retinal reattachment. Methods Prospective case series of 26 patients who presented to the Wolverhampton Eye Infirmary with a primary rhegmatogenous macula-off retinal detachment. Macular detachment height was assessed by B-scan ultrasound (10 Mhz) in the seated and supine postures before surgery. Age, gender, duration of the detachment, type of surgery, preoperative (pre-op) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 11 publications
1
36
0
Order By: Relevance
“…Factors previously reported to be associated with functional recovery after macula-off RRD included preoperative VA, 12 duration of macular detachment, 6,8 height of macular detachment, 13,14 and age. 12 In the present study, the presence of a foveal bulge was the only significant independent predictor of final BCVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors previously reported to be associated with functional recovery after macula-off RRD included preoperative VA, 12 duration of macular detachment, 6,8 height of macular detachment, 13,14 and age. 12 In the present study, the presence of a foveal bulge was the only significant independent predictor of final BCVA.…”
Section: Discussionmentioning
confidence: 99%
“…5 Persistent functional damage to the macula is observed in a proportion of eyes affected by macula-off RRD. [6][7][8][9][10][11] Factors reportedly associated with functional recovery following macula-off RRD include preoperative VA, 12 duration of macular detachment, 6,8 height of macular detachment, 13,14 and age. 12 Even among eyes predicted to have good postoperative vision due to good preoperative conditions and the absence of significant complications during surgery, some eyes continue to have poor VA.…”
mentioning
confidence: 99%
“…Another recent study has established the height of macular detachment as a statistical predictor of postoperative visual acuity. Supposedly, the shallower the macular detachment is, the greater the likelihood is of a good visual outcome is supposed to be (Mowatt et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The few studies on the influence of the height and the duration of the macular detachment on the postoperative recovery of VA [23], [24] found that - within the first week of macular detachment - a lower height of macular detachment was associated with better postoperative visual acuity. Furthermore, previous studies relate to the outcomes for patients who have undergone “conventional” (buckling) surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[2], [9], [11], [14], [18][22] However, in recent years trans pars plana vitrectomy (TPPV) is often used as a primary procedure, which might affect postoperative recovery. [30] Finally, follow-up periods in these studies ranged from 3 to 24 months, [2], [9], [11], [14], [18]–[21], [23], [24] whereas it is known that postoperative VA can improve gradually, reaching a maximum value between 6–12 months postoperatively. [10], [31] …”
Section: Introductionmentioning
confidence: 99%